Model Pelayanan Sosial Panti dan Non Panti di Lembaga Kesejahteraan Sosial Anak (LKSA) Anak Gembira - Debora Manalu; Berlianti, Berlianti (Yayasan Literasi Sains Indonesia, 2024)
This research aims to find out the implementation of home-based and non-antibased social service models implemented at the Child Social Welfare Agency (LKSA) Anak Gembira. LKSA Anak Gembira is an institution that provides social services for children who need protection and welfare. The research method in this study is descriptive qualitative which describes the model of social services based on orphanages and non-orphanages. Data were collected through observation, interviews, and analysis of related documents. Consisting of 10 research informants, 1 key informant, 6 main informants and 3 additional informants. The institution-based social service model applied is an institutional-based social service model. The non-anti-based social service model uses a family-based social service model. The implementation of the institution-based and non- institution-based social service models at LKSA Anak Gembira still has several shortcomings, including the unoptimal use of the Rumah Pertolongan in providing social services to children outside the orphanage, the absence of BPJS Health cards for children living in the orphanage, and the unavailability of professional social workers who can provide counselling services to children in the orphanage and the absence of a special room to carry out counselling activities in the orphanage. The result of this research is that in providing social services at LKSA Anak Gembira, it has implemented two social service models, namely the orphanage and non-orphanage models, so that this can be an encouragement for other orphanages or LKSA to also implement this social service model.